Hubungan antara Kadar Hemoglobin dengan Terjadinya Kejang Demam pada Anak Usia Balita - Ruri Diptaswari Pratiwi; Anak Agung Oka Lely; Ni Made Hegard Sukmawati (Aesculapius Medical Journal, 2023)
[The Relationship Between Hemoglobin Levels With The Occurrence Of Fever Seizures In Toddler Age Children] Febrile seizures are neurological disorders commonly found in children. This disease can be caused by the level of hemoglobin. If the hemoglobin level is low, it can cause anemia. Anemia has an impact on decreasing the power of oxygen transportation to the tissues which disrupts the stability of the nerve cell membranes and triggers seizures. The purpose of the study was to find out the correlation of hemoglobin levels with the emergence of febrile seizures that attacked children under five years old at the Sanjiwani Hospital, Gianyar Regency for the 2017-2019 period. This study used secondary data obtained from the patient's medical history, with a cross-sectional design. The total sample is 96 respondents, obtained by simple random sampling. With statistical analysis, there was no significant difference regarding gender (p=0.636) and age (p=0.619) between the febrile seizure group and the febrile group without seizures. Unpaired t-test results show that the mean hemoglobin level in subjects with febrile seizures is 10.71gr/dl, whereas in subjects with fever without seizures, the average hemoglobin level is 12.02g/dl. This difference was statistically significant (p<0.001). In this study, the relationship between low Hb levels and the incidence of febrile seizures was analyzed. With the chi-square test (Ï‡2), there was a significant correlation between patients with low Hb levels (Hb < 11 g/dl) and the occurrence of febrile seizures (p < 0.001, RP = 2.1 CI 1.531-2.893). It can be concluded in this study that there is a correlation between hemoglobin levels and the occurrence of febrile seizures that attack children under five years old at the Sanjiwani Hospital, Gianyar Regency. Keywords : febrile seizures, children under five, hemoglobin